A case of dysphagia and microcytic anemia successfully treated with heme iron polypeptide - Makadia, Rajesh (International Journal of Research in Medical Sciences, 2024)
A 40-year-old female presented to the oncologist with complaints of dysphagia (pain while swallowing) for the past month. Apart from this symptom, she had no other significant clinical complaints. Physical examination and imaging did not reveal any obvious findings, except for a few non-specific left supraclavicular lymph nodes. Blood tests revealed anemia, for which she was prescribed heme iron polypeptide (HIP). Follow-up over six months showed significant improvement in her hemoglobin levels and resolution of symptoms. This case highlights the efficacy and gastrointestinal tolerability of HIP in managing anemia.